Disrupted childhoods : children of women in prison - Siegel, Jane A., 1949- (Rutgers series in childhood studies., 2011)
Disrupted Childhoods explores the issues that arise from a mother's confinement and provides first-person accounts of the experiences of children with moms behind bars. Jane A. Siegel offers a perspective that recognizes differences over the long course of a family's interaction with the criminal justice system. Presenting an unparalleled view into the children's lives both before and after their mothers are imprisoned, this book reveals the many challenges they face from the moment such a critical caregiver is arrested to the time she returns home from prison.